2017
DOI: 10.15439/2017f224
|View full text |Cite
|
Sign up to set email alerts
|

A Decision Support System for Demand Forecasting based on Classifier Ensemble

Abstract: Abstract-Demand forecasting is the process of constructing forecasting models to estimate the quantities of several products that customers will purchase in the future. When the warehouse and the number of products grow, forecasting the demand becomes dramatically hard. Most of the demand forecasting models rely on a single classifier or a simple combination of these models. In order to improve demand forecasting accuracy, we investigate several different classifiers such as MLP, Bayesian Network, Linear Regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…An extensive literature survey has revealed that there are two main types of methodologies that are applied in the domain of product demand forecasting problems [11]. These are: i) stand-alone forecasting models and ii) hybrid forecasting models combining multiple models together.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…An extensive literature survey has revealed that there are two main types of methodologies that are applied in the domain of product demand forecasting problems [11]. These are: i) stand-alone forecasting models and ii) hybrid forecasting models combining multiple models together.…”
Section: Literature Reviewmentioning
confidence: 99%
“…An Integrated Case-Based Reasoning and ANN model was successfully implemented to predict product unit cost for mobile phone companies in Taiwan [16]. A similar study proposed by Islek et al [11] successfully merged various models, i.e., multi-layer perceptrons with Bayesian networks, linear regression and support vector machines to predict product demands in a real data set derived from a dried fruits and nuts company from Turkey.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The authors of [18] proposed using the Dynamic Artificial Neural Network for food sales forecasting for one of multiplexes in India. In the paper [19], different classifiers were analysed and a proposition of combining various forecasting models using neural network was presented in order to improve results for forecasting demands of warehouses. Experiments were performed on real sales data of a national dried fruits and nuts company from Turkey.…”
Section: Related Workmentioning
confidence: 99%
“…By combining various machine-learning models; it will help to resolve issues of warehouse forecasting. Hence, the devised method's forecast error is less than 5% compared to predicting through a single model for forecasting methods; thus, the combined variants reveals better performance (ISLEK, S. G. O 2017).…”
Section: Introductionmentioning
confidence: 99%